ANALISIS PENGARUH INTERMEDIASI PERBANKAN, BI RATE, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI (STUDI JAWA TIMUR PERIODE 2007-2016) - Ditalistya, Risma (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aimed to examine the effect of banking intermediation, inflation, and BI Rate on economic growth in the region of East Java.  The author uses economic growth  as the dependent variable and include variables of loan to deposit ratio, BI rate, and inflation as an independent variable. The author uses quantitative research methods and using multiple linear regression analysis using OLS during period 2007-2016.The  results  showed  that  the  variable  BI  Rate  significant  and negative influential on economics growth in East Java, while the inflation and loan to deposit ratio influence significantly and positive on economics growth in East Java.Keywords: Economic Growth,  Loan to Deposit Ratio, BI Rate, and Inflation